PENDIDIKAN DALAM PERSPEKTIF STRUKTURAL KONFLIK - Nur Rohman (Bahasa Indonesia, 2020)
Structural conflict is the antithesis of structural theory functional, where the structural theory functional very put forward the regularity in society. Perspective of conflict have a different from the functional perspective a more see a positive contribution educational institutions for the community. This perspective more emphasis on the role of power( not recognize similarities in a society). As well as in the school, education is a class variables or status.